Kogabwilhan's Determination Strategy in Keeping the Security of the Border Areas In South China Sea Defense Management Perspective - Manurung, Yanto; Saragih, Herlina; Sarjito, Aris (Graduate Program Magister Manajemen Pendidikan, 2022)
This study discussed Kogabwilhan's deterrence strategy in maintaining the security of the border area in South China Sea from a defense management perspective. To anticipate the emergence of threats that can interfere with national interests, the establishment of the Kogabwilhan is primarily aimed at preparing for handling crises in the territory of Indonesia. This study belongs to library research. The results showed that management function, there are five main functions which are further elaborated as follows. First, the leader or manager does the planning, and what will be done. Then, organize to implement the plan, and then assemble the organization's personnel with the necessary resources to implement the plan. Indonesia needs to strengthen its military strength in the Natuna area. To overcome potential conflicts in the South China Sea, it needs conducting a series of exercises in the Natuna Sea.